Analisis Kapasitas Produksi Dengan Metode MTM-1 Dan Alat Bantu Promodel Dalam Pembuatan SOP Perbaikan (Studi Kasus: PT. Karya Utama Pratiwi) - SUGIOKO, ANDRE; -, Denys; Hidayat, Trifenaus Prabu (Metris: Jurnal Sains dan Teknologi, 2021)
PT. Karya Utama Pratiwi is a company that produces socks from yarn to socks. This company has two parts: the manufacture of socks and the heating section. There are still manual processes in the heating section, or there is still much human intervention. On the contrary, what happens in the sock-making section, which has many machines. The problem that occurs today is that the achievement of production targets is not always achieved, namely as many as 520 finish goods (18720 socks), so the root of the problem is sought. It was found that the production capacity measurement was never carried out, so it becomes the background of research in this study to measure production capacity in the heating section. Capacity measurement begins with measurements at each work station using a predetermined time standard system by paying attention to work movements using the MTM-1 method as input to the ProModel. Initial system simulation results produced an average of 478 in 30 replications. In addition, there are entities experiencing login delays of 10.36 and 21.20 minutes. In some locations, it was seen that they experienced idle time. For example, the oven was 56.97%, above 50%. So, there need to be improvements in order to achieve the target. These things become the basis for making SOPs achieve targets; SOPs are designed and run with ProModel simulations based on possible assumptions. Based on the SOP simulation results, increase production by 2% from the maximum initial simulation conditions from 579 to 594. SOPs will help meet targets and are well executed.